Infection related glomerulonephritis due to scrub typhus in paediatric population: A case series and literature review - Khuntdar, Bidyut Kumar; Guchhait, Riya; Roy, Arghy Kamal (Asian Journal of Medical Sciences, 2022)
Background: Infection-related glomerulonephritis (IGRN) is an immune-complex mediated renal injury occurring simultaneously with the infection. Till date, though rare, all the reported cases of IRGN were caused by either Streptococcus spp. or Staphylococcus spp. Emerging suggestive risk factors for IRGN were diabetes mellitus, malignancy, HIV infection, and alcoholism. IRGN following Rickettsial infection, its disease course, and fatality are unknown. Aims and Objectives: In the pediatric population most of the cases are diagnosed as post-infection glomerulonephritis that occurred after a latent period. Here we have presented five typical cases of IRGN with its complication caused by atypical organism. From both points of view, the case series is rare and unique. Materials and Methods: The authors report five cases of IRGN in scrub typhus infection that illustrate the difficulty of its diagnosis and do a brief review of the literature on this topic. Results: All the five cases were presented with fever, without any Eschar except one. Moreover, they presented with bizarre renal symptoms confounding diagnosis. All the cases had neutropenia and lymphocytosis that was the sole finding to point toward scrub typhus. But none of our cases had developed acute kidney injury as such. Conclusion: Scrub typhus is an acute febrile illness. Hence, patients with nephritic presentation should be evaluated for Scrub typhus infection if associated with long-term unresolving fever.